Fictions of state : culture and credit in Britain, 1694-1994 - Brantlinger, Patrick, 1941- (Cornell University Press, 1996)
In this ambitious book, Patrick Brantlinger offers a cultural history of Great Britain focused on the concept of ""public credit, "" from the 1694 founding of the Bank of England to the present.